2013
DOI: 10.1371/journal.pone.0059742
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Use, Blood Lead Levels, and Attention Deficit Hyperactivity Symptoms in Children: A Longitudinal Study

Abstract: BackgroundConcerns have developed for the possible negative health effects of radiofrequency electromagnetic field (RF-EMF) exposure to children’s brains. The purpose of this longitudinal study was to investigate the association between mobile phone use and symptoms of Attention Deficit Hyperactivity Disorder (ADHD) considering the modifying effect of lead exposure.MethodsA total of 2,422 children at 27 elementary schools in 10 Korean cities were examined and followed up 2 years later. Parents or guardians wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 46 publications
5
54
0
1
Order By: Relevance
“…These factors may interact and do not always imply causality. They range from divorce (Allen, 2010), poverty (Russell, Ford, Rosenberg, & Kelly, 2013), parenting styles (Johnston, Mash, Miller, & Ninowski, 2012), low maternal education, lone parenthood and reception of social welfare ((Hjern, Weitoft, & Lindblad, 2010), sexual abuse (Weinstein, Staffelbach, & Biaggio, 2000), lack of sleep (Thakkar, 2013), heritability (Larsson, Chang, D’Onofrio, & Lichtenstein, 2013) and perinatal issues (Schmitt & Romanos, 2012) to eczema (Schmitt, Buske-Kirschbaum, & Roessner, 2010), artificial food additives (McCann et al, 2007), mobile phone use (Byun et al, 2013) and growing up in areas with low solar intensity (Arns, van der Heijden, Arnold, & Kenemans, 2013). All these factors and more may play a role when a particular child exhibits impairing hyperactive and inattentive behaviours, and there is no conclusive cause of ADHD.…”
Section: There Is No Single Cause Of Adhdmentioning
confidence: 99%
“…These factors may interact and do not always imply causality. They range from divorce (Allen, 2010), poverty (Russell, Ford, Rosenberg, & Kelly, 2013), parenting styles (Johnston, Mash, Miller, & Ninowski, 2012), low maternal education, lone parenthood and reception of social welfare ((Hjern, Weitoft, & Lindblad, 2010), sexual abuse (Weinstein, Staffelbach, & Biaggio, 2000), lack of sleep (Thakkar, 2013), heritability (Larsson, Chang, D’Onofrio, & Lichtenstein, 2013) and perinatal issues (Schmitt & Romanos, 2012) to eczema (Schmitt, Buske-Kirschbaum, & Roessner, 2010), artificial food additives (McCann et al, 2007), mobile phone use (Byun et al, 2013) and growing up in areas with low solar intensity (Arns, van der Heijden, Arnold, & Kenemans, 2013). All these factors and more may play a role when a particular child exhibits impairing hyperactive and inattentive behaviours, and there is no conclusive cause of ADHD.…”
Section: There Is No Single Cause Of Adhdmentioning
confidence: 99%
“…Previous studies found hyperactivity and ADHD associated with problematic internet use (Kaess et al 2014;Ko et al 2012;Kormas et al 2011;Ozturk et al 2013) and using the mobile phone for entertainment (playing games, internet) (Byun et al 2013b;Zheng et al 2014). Hyperactive adolescents are easily distracted, show problems in sustaining attention and are less capable of impulse control (Douglas 1972).…”
Section: Behaviour and Problematic Mobile Phone Usementioning
confidence: 99%
“…However, this was not done so far, although impaired well-being (Byun et al 2013a;Redmayne et al 2013) and Attention Deficit Hyperactivity Disorder (ADHD) symptoms (Byun et al 2013b) were linked to amount of mobile phone use in children and adolescents. Thus, it remains unclear, if these adverse effects in adolescents may be attributed to problematic use of the mobile phone or amount of mobile phone use.…”
Section: Introductionmentioning
confidence: 99%
“…Korean children (Byun et al 2013) or inattention in 7,102 Chinese adolescents (Zheng et al 2014). But interestingly, they found mobile phone use for playing games (Byun et al 2013) and the time spent on the mobile phone for entertainment (Zheng et al 2014) being associated with ADHD symptoms and inattention, respectively.…”
Section: Introductionmentioning
confidence: 98%